Virtual reality in posturography. - Tossavainen, T.
Balance dysfunctions are common, especially among elderly people. Present methods for the diagnosis and evaluation of severity of dysfunction have limited value. We present a system that makes it easy to implement different visual and mechanical perturbations for clinical investigations of balance and visual-vestibular interaction. The system combines virtual reality visual stimulation with force platform posturography on a moving platform. We evaluate our construction's utility in a classification task between 33 healthy controls and 77 patients with Meacuteniegravere's disease, using a series of tests with different visual and mechanical stimuli. Responses of patients and controls differ significantly in parameters computed from stabilograms. We also show that the series of tests achieves a classification accuracy slightly over 80% between controls and patients
Keywords: Meniere's disease; Balance dysfunction; Elderly people; Force platform posturography; Mechanical perturbation; Stabilogram; Virtual reality visual stimulation; Visual perturbation; Visual-vestibular interaction